El uso de los recursos tecnológicos educativos y su incidencia en el proceso de interaprendizaje en los estudiantes de educación básica superior de la unidad educativa "11 de octubre", cantón Urdaneta, periodo lectivo 2021-2022 - Campana Deca, María Leonor (2022)
Education is the basis on which a society is based, a society that is constantly changing, being today the technology that allows strengthening the knowledge acquired by students and an essential tool for teachers. The objective of this research work is to analyze how ICT skills and competencies affect the use of educational technological resources by teachers of the Educational Unit “October 11” in the development of activities related to their daily work and how these affect the inter-learning process of higher basic education students. The work has a theoretical basis the same one that exposes the subject, based on theoretical foundations. The design of the research responds to two modalities: bibliographic and field, where different criteria of various authors on educational technological resources and their influence on the inter-learning process have been detected, expanded and deepened. The qualitative-quantitative methodology was used, working with the entire population consisting of 42 teachers, the information was obtained through interviews and surveys with which domain and technological skills were analyzed. As a result, an average level of ICT skills was obtained from teachers that affects the use of technological resources for their daily work, this due to the lack of training in issues related to educational technology, on the other hand, traditionalism maintains some teachers unrelated to the use of digital technological resources. In conclusion, it is necessary to promote and strengthen the technological skills of teachers, promoting an innovative culture at the forefront of the current era to achieve better performance and professional training of the institution's faculty